Achieving Sustainable Energy Security: 2030 Outlook for ASEAN, People Republic of China and India - Ying Fan; Biswa Nath Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2015)
The rapid growth of ASEAN economies, the People's Republic of China and India (called ACI henceforth) — major drivers of Asia and the world economy—during the last five decades has caused significant strains on their scarce resources, particularly energy and contributed to serious problems of energy security, environmental degradation and climate change. In coming decades, these economies are expected to witness high growth, lack of adequate traditional energy sources, high dependence on imported energy, heavy reliance on energy-intensive industries, and rising transportation demands. In the coming decades, their energy demand may create serious challenges in terms of energy security. Adopting sustainable and innovative management practices and policies for key resources such as energy and mitigating environment and climate change problems are among major common challenges for all the ACI economies. This paper examines primarily on the ACI's sustainable energy security outlook until 2030 through an overview of the ACI's energy resources, production mix, consumption mix, emissions of greenhouse gases, and the state of the development of renewable, clean and new energy. The paper projects the ACI's energy demand and its impact on carbon dioxide emissions until 2030 under different policy scenarios using a Computable General Equilibrium (CGE) analysis. Furthermore, the paper evaluates ACI's sustainable energy security situation through examining ACI's energy self-sufficiency, dependence on imported energy, energy import diversification transportation security and energy infrastructure financing. Lastly it provides some policy recommendation to achieve sustainable energy security in ACI.
Keywords: Q43; Q47; R13; Q50; Q31; Q20; O53; C68; 330; energy demand and security; sustainable energy; ASEAN; India and People Republic of China; environment and climate change